PROFIT OPTIMIZATION OF RICE FARMING BUSINESS ENTITIES IN JASMINE VILLAGE, DELI SERDANG - Nisa Khairani; Dedy Juliandri Panjaitan; Rina Widyasari (Pena Cendekia Insani, 2021)
This study aims to optimize the yield from rice farming in Melati village. Theresults of the calculation of profit optimization using the simplex method. Thisresearch uses primary and secondary data. The problem in this study is the lackof capital and labor so that the results of agricultural income have not reachedoptimum due to the lack of raw materials needs by agriculture. The purpose ofthis research is to solve the problem of limited resources optimally by usinglinear functions and to find out how to apply them well in maximizing optimalprofits.